Minha massinha - Bernhardt, Cristiane Otilia Colossi; Silva, Luzinete Conceição Da; Santos, Marcia Barbosa Cassia dos; Mamedes, Norenir Oliveira Leite (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2022)
>>> ver pdf